Характер прояву зимостійкості та врожайності сортів пшениці м’якої різного типу розвитку залежно від умов вирощування - Базалій, В.В.; Бойчук, І.В.; Ларченко, О.В.; Бабенко, Д.В.; Базалій, Г.Г. (Фактори експериментальної еволюції організмів, 2013)
Aims. One of the main causes of unstable grain production of winter wheat in the southern zone of soft Steppes of Ukraine is the weather conditions during the growing season and winter. Soft winter wheat varieties Odesskaya 267, Dryada 1, Znahidka odesskaya, Kharus own hiqh winter hardiness stable of it’s manifestation in different growing conditions. Variety of alternative types Solomia, Clarissa showed yields at late times of sowing at the optimum so they must be used at a later date for planting, as well as insurance culture in passages dead of winter wheat crops, and how to sow spring crops in the «Februarys windows» and early spring. Methods. In the State Register of plant vrietes of Ukraine writed studies of winter wheat varieties at different soft-genetic and ecological origins. Results. Further development of the crop, the resistance to the harsh winter and the final result depends on the quality of sowing in autumn because the basics of winter wheat yields are formed during early plant development. Conclusions. Varieties resistant to stressful situations have a relatively low rate of response to changes in growth conditions, they have regression coefficient less than 1 with its further decline, resistance to adverse conditions varieties increases. Key words: soft winter, insurance culture, early spring, wheat varieties, yields.